Biliary complications in transplant patients: A comparison of two ERCP diagnostic methods (2013)
ABSTRACT:Background: Biliary complications after liver transplantation are a serious cause of morbidity and mortality. Direct invasive cholangiography techniques, endoscopic retrograde cholangiography (ERCP) and percutaneous transhepatic cholangiography (PTC) all have procedure-related complications. Ultrasonography and magnetic resonance cholangiopancreatography (MRCP) are non-invasive, safe, and accurate. Objective: The aim of this study was to evaluate the use of US and MRCP for detecting biliary complications following liver transplantation and compare these findings with those from the gold standard, ERCP. Methods: Between march 2006 and January 2009, twenty-seven consecutive liver transplant recipients at the Hospital Pablo Tobón Uribe in Medellín-Colombia who presented clinical and biochemical evidence of biliary complications were evaluated with US, MRCP and ERCP. Results: The presence of a biliary anastomotic complications was confirmed in 26 patients (92.6%), anastomotic biliary strictures in 24 (88.9%), ischemic or diffuse intrahepatic biliary strictures in two (7.4%), and choledocholithiasis in one (3.7%). All patients underwent ERCP, 25 underwent US (92, 5%) and 13 underwent MRCP (48, 1%). There was a statistically significant correlation for MRCP and ERCP findings, but not for US findings. The sensitivity of MRCP was 80% and its specificity was 50%. The sensitivity of US was 55.6% with 50% specificity. Positive and negative predictive values for MRCP were 92.3% and 25%, but for US were 93.7% and 7.8% respectively. Conclusions: MRCP is an accurate imaging tool for assessment of biliary complications after liver transplantation. We recommend that MRCP be the diagnostic imaging modality of choice in this setting, reserving direct cholangiography for therapeutic procedures.